(3GdeMQQ GdeNJUQ ef GdebQQ GdeNJUQ ef GdecQQ aj bhGYO bQGAI fGaY hQhGjI bGdhf hhQTs - (3fGUQ Hf YHO GdMajX Hf YHO Gddg Hf GdegdGs ((3eMeO Hf UGdM Gdeci s)
(3ChdgG (B:s
(3hHYO , agPG GdeNJUQ GdeMQQ ef cJGH GdebQQ GdPi ENJUQJg ef GdecQQ , CQOJ Cf COeY ajg bhGYO bQGAI fGaY , hCPcQ eG EJab Ydjg QhGjGg heG ENJdafG ajg s
(3BNQgG (B:s
(3eJUd Edi QShd Gddg Udi Gddg Ydjg hidg hSde ePchQ ai GdJjSjQ hcGfJ GdbQGAg GdePchQI hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdbQGAGJ hGdJLhjOs